Statistics in usability tests: Roll up your sleeves and have no fear - Marcos, Mari-Carmen (Anuario ThinkEPI, 2015)
Within a website design process, usability evaluation is a key step to ensure success. Among the various evaluation methods, user testing provides information about potential performance problems, such as the effectiveness and efficiency with which users perform tasks on the web. In this context of evaluation and performance measurement, statistics is a tool that provides validity and reliability to the tests´ results, and delivers the evidence needed to make better design decisions.
Keywords: Statistics; User testing; User experience; UX; Usability; Metrics.